THE EFFECT OF USING THINK-TALK-WRITE(TTW) MODEL ON STUDENTS’ WRITING ABILITY OF DESCRIPTIVE TEXT - merry agnesmonikalimbong merryagnesmonikalimbong (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The aim of this research are to know: 1) the application of think-talk-write(TTW) model on teaching writing descriptive text ability, 2) students writing descriptive text ability before and after using think-talk-write(TTW) model, 3) whether there any significant effect of think-talk-write(TTW) model on teaching writing descriptive text ability at the eighth grade students of SMP Negeri 3 Satu Atap Sosorgadong. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the VIII grade students’ of SMP Negeri 3 Satu Atap Sosorgadong which consist of 71 students. Sample were VIII A which consist of 22 students which taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instruments. The result of this r esearch: 1) the application of think-talk-write(TTW) model was 3.7, it was categorized “Very Good”. 2) the mean score of the students’ writing descriptive text ability was 51 and it was categorized “ Bad”. Meanwhile, after using think-talk-write(TTW) model was 77 it is categorized “ Good”. The result of data analysis shows that ttest was higher that ttable(ttest 12.38>ttable 2.08). So. The hypothesis was accepted. It means that, there is any significant effect of think-talk-write(TTW) model on students’ writing descriptive text ability at the VIII grade students of SMP Negeri 3 Satu Atap Sosorgadong in 2020/2021 Academic Year.